The Experimental Platform Design for NCS Based on CAN Bus - Zhao Weiquan; Yuan Huaqiang; Wei Xiaorui (International Journal of Reconfigurable and Embedded Systems (IJRES), 2015)
In order to facilitate research on the performance of Networked Control System, overcome the defects of unable to reflect the system performance, based on the CAN bus a kind of NCS experimental platform is designed. The system is composed of a main node and several slave nodes and Dc motor as the actuator. The master node is designed with ARM + U-boot + Linux structure, connecting with PC via Ethernet. For this experiment platform, using c + + Builder a scheduling algorithm performance testing software is developed, to further research on the effects of different scheduling algorithm on the NCS performance.